Investigating Adaptive Regulatory Evolution of Intracellular Arginine Metabolism in Salmonella Typhimurium - Perry, Jordyn N. (My University, 2022)
Salmonella enterica is a facultative intracellular pathogen capable of eliciting severe, systemic disease necessitating antibiotic intervention. Systemic infection is facilitated by intracellular replication within host immune cells, which is enabled by complex regulatory networks governed by two-component systems (TCSs). Intracellular-active TCSs sense antimicrobial chemical cues in the microenvironment and respond adaptively through transcriptional regulation to support intracellular survival. SsrA/SsrB and PhoQ/PhoP are two essential TCSs that elicit a robust defense against host immunity by regulating clusters of virulence genes and integrating novel targets to support regulon expansion and enhance pathogenicity. Metabolic adaptation is critical to bacterial survival and can initiate host-pathogen interactions that influence infection outcome. Further, mitigation of host immunity by manipulation of arginine metabolism has been documented in intracellular pathogens. Herein, I investigated TCS-mediated regulatory evolution pertaining to arginine metabolism, hypothesizing that adaptations to metabolic regulation might confer a fitness advantage to Salmonella replicating intracellularly. I explored intracellular regulation of de novo biosynthesis and extracellular import of arginine, establishing PhoP-mediated regulation of arginine transport. I determined that arginine transport contributes to bacterial fitness in macrophages and began to investigate the mechanism by which arginine importation enriches for intracellular replication. This work informs on evolutionary mechanisms that serve to enhance virulence in Salmonella and provides further insight into our understanding of the intracellular lifestyle of infection.
Investigating Arginine Metabolism in Salmonella Typhimurium
Keywords: Salmonella; bacterial pathogenesis; bacterial metabolism; host-pathogen interactions